Redox-Programmable Spin-Crossover Behaviors in a Cationic Framework - Wu, Si-Guo; Wang, Long-Fei; Ruan, Ze-Yu; Du, Shan-Nan; Gómez-Coca, Silvia; Ni, Zhao-Ping; Ruiz, Eliseo; Chen, Xiao-Ming; Tong, Ming-Liang (Journal of the American Chemical Society, 2022)
Metal-organic frameworks (MOFs) provide versatile platforms to construct multi-responsive materials. Herein, by introducing the neutral tetradentate ligand and the linear dicyanoaurate(I) anion, we reported a rare cationic MOF [FeII(TPB){AuI(CN)2}]I·4H2O·4DMF (TPB = 1,2,4,5-tetra(pyridin-4-yl)benzene) with hysteretic spin-crossover (SCO) behavior near room temperature. This hybrid framework with an open metal site (AuI) exhibits redox-programmable capability toward dihalogen molecules. By means of post-synthetic modification, all the linear [AuI(CN)2]- linkers can be oxidized to square planar [AuIII(CN)2X2]- units, which results in the hysteretic SCO behaviors switching from one-step to two-step for Br2 and three-step for I2. More importantly, the stepwise SCO behaviors can go back to one-step via the reduction by l-ascorbic acid (AA). Periodic DFT calculations using various SCAN-type exchange-correlation functionals have been employed to rationalize the experimental data. Hence, these results demonstrate for the first time that switchable one-/two-/three-stepped SCO dynamics can be manipulated by chemical redox reactions, which opens a new perspective for multi-responsive molecular switches.Metal-organic frameworks (MOFs) provide versatile platforms to construct multi-responsive materials. Herein, by introducing the neutral tetradentate ligand and the linear dicyanoaurate(I) anion, we reported a rare cationic MOF [FeII(TPB){AuI(CN)2}]I·4H2O·4DMF (TPB = 1,2,4,5-tetra(pyridin-4-yl)benzene) with hysteretic spin-crossover (SCO) behavior near room temperature. This hybrid framework with an open metal site (AuI) exhibits redox-programmable capability toward dihalogen molecules. By means of post-synthetic modification, all the linear [AuI(CN)2]- linkers can be oxidized to square planar [AuIII(CN)2X2]- units, which results in the hysteretic SCO behaviors switching from one-step to two-step for Br2 and three-step for I2. More importantly, the stepwise SCO behaviors can go back to one-step via the reduction by l-ascorbic acid (AA). Periodic DFT calculations using various SCAN-type exchange-correlation functionals have been employed to rationalize the experimental data. Hence, these results demonstrate for the first time that switchable one-/two-/three-stepped SCO dynamics can be manipulated by chemical redox reactions, which opens a new perspective for multi-responsive molecular switches.